Comparisons of automated blood pressures in a primary health care setting with self-measurements at the office and at home using the Omron i-C10 device. Issue 2 (April 2015) - Al-Karkhi, Isam; Al-Rubaiy, Raad; Rosenqvist, Ulf; Falk, Magnus; Nystrom, Fredrik H.
Abstract : Objective: We aimed to compare blood pressure (BP) levels recorded using the semiautomatic oscillometric Omron i-C10 BP device in patients with or without hypertension in three different settings: (a) when used by a doctor or a nurse at the office (OBP); (b) when used for self-measurement by the patient at the office (SMOBP); and (c) when used for 7 consecutive days at home (HBP). Materials and methods: A total of 247 individuals were invited to participate, but 78 of these individuals declined and a further seven were excluded, leaving a final cohort of 162 participants. Results: The mean OBP was higher than HBP (difference 8.1±14/3.1±8.8 mmHg, P <0.0001) and so was SMOBP compared with HBP (difference 7.0±13/4.2±7.3 mmHg, P <0.0001). Sixteen participants (9.9%) had at least 10 mmHg higher systolic SMOBP than OBP and 28 (17%) participants had at least 10 mmHg lower systolic SMOBP than OBP. Participants who were current smokers had a larger mean difference between systolic OBP and SMOBP than nonsmokers (OBP−SMOBP in smokers: 6.6±9.4 mmHg, OBP−SMOBP in nonsmokers: 0.5±9.2 mmHg, P =0.011 between groups). Conclusion: Self-measurement of BP in the office does not preclude an increase in BP when levels in the individual patients are compared with HBP using the same equipment. Thus, SMOBP with a semiautomatic device does not lead to a reduction in the white-coat effect in the same manner as fully automatic devices.